Dealing with Wicked Problems: Conducting a Causal Layered Analysis of Complex Social Psychological Issues - Bishop, Brian John; Dzidic, Peta (Springer New York LLC, 2014)
Causal layered analysis (CLA) is an emerging qualitative methodology adopted in the discipline of planning as an approach to deconstruct complex social issues. With psychologists increasingly confronted with complex, and “wicked” social and community issues, we argue that the discipline of psychology would benefit from adopting CLA as an analytical method. Until now, the application of CLA for data interpretation has generally been poorly defined and overwhelming for the novice. In this paper we propose an approach to CLA that provides a method for the deconstruction and analysis of complex social psychological issues. We introduce CLA as a qualitative methodology well suited for psychology, introduce the epistemological foundations of CLA, define a space for it adoption within the discipline, and, outline the steps for conducting a CLA using an applied example.